Commonplaces - Spears, Rebecca Ann (Ars Medica, 2019)
These six poems, "Commonplaces," "Still Life, with Questions," "Daddy-o," "Notes on Extremities," "On Her Way," and "Before, Childless and Wanting," focus on issues of concern to care-takers and relatives of those who are ill, infertile, aging, or dying. "Commonplaces" views the mortality/immortality of our physical bodies, considering the law of conservation of mass. "Still Life, with Questions" addresses the loss of love and the mortality of an "ex." "Daddy-o," written for Father's Day, considers my father's loss of eyesight (through glaucoma and cateracts). "Notes on Extremities" is a response to a loved one's death from multiple sclerosis. "On Her Way" affirms a dying mother, and how we say good-bye. The daughter "provisions" the mother for her journey. The setting of "Before, Childless and Wanting" is a long train ride. The observer, who is childless, watches a child "on the loose," wandering the aisle, while the mother reads and then falls asleep. This poem employs longing, discovery, and surprise.